High Gain and Reduced Switch Stress DC-DC Converter Topology for PV System (International Journal of Engineering and Computer Science, 2018)
This paper presents a new high step-up isolated DC-DC converter topology for photovoltaic system. The suggested configuration provides a converter with high voltage gain and reduced switch stress by using three coupled inductor with two hybrid voltage multiplier cell. The operation of the proposed converter is based on a charging capacitor with a single switch in its structure. A passive clamp circuit composed of capacitors and diodes is employed in the converter structure for lowering the voltage stress on the power switch as well as increasing the voltage gain of the converter. Since the voltage stress is low in the provided topology, a switch with a small ON-state resistance can be used. As a result, the losses are decreased and the efficiency is increased. The design of DC-DC boost converter is also discussed in detail. Simulation of DC-DC converter is performed in MATLAB/Simulink and the result are verified